With the Newsroom at Home: Routines and Tensions of Women Journalists in Times of Covid-19 (2021)
This article identifies the routines and working practices of women journalists from Colombia and Venezuela in the framework of the health emergency caused by covid-19 in the countries where they work. It is a quantitative research at a descriptive cross-sectional level in which an instrument made up of 26 questions organized into five categories of analysis was used. Categories include family–work relationship, working life, and health and well-being, and the questionnaire was applied to 110 professionals from Colombia and Venezuela. It was found that the compulsory confinement hastened the insertion of journalists in the use of information and communication technologies, applications, and software for content production. Although they were already working in digital media, they had to develop new skills in this field. For 47% of them, their working hours were extended for more than 3 hours a day, which for 79% represents family tensions, given that 38% have underage children or older adults under their care. However, during the confinement, their participation in the formation of public opinion was also expanded through their personal social networks, incorporating corruption issues and citizen complaints. Regarding their routines, it is concluded that the pandemic transformed access to information sources, newsrooms, and, therefore, the dynamics of news production, so we are faced with a new way of doing journalism that puts reporting and ethics into tension with information and communication technologies.